2019
DOI: 10.1111/hiv.12711
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a hepatitis C continuum of care among HIV/hepatitis C virus‐coinfected individuals in EuroSIDA

Abstract: Objectives The aim of the study was to establish a methodology for evaluating the hepatitis C continuum of care in HIV/hepatitis C virus (HCV)‐coinfected individuals and to characterize the continuum in Europe on 1 January 2015, prior to widespread access to direct‐acting antiviral (DAA) therapy. Methods Stages included in the continuum were as follows: anti‐HCV antibody positive, HCV RNA tested, currently HCV RNA positive, ever HCV RNA positive, ever received HCV treatment, completed HCV treatment, follow‐up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Among our study population, one PWID presented with acute HCV infection at BL and showed persisting viraemia at FU. Although the overall test rate in our population was high, this goes in line with recently published findings from the EuroSIDA cohort, where in almost 20% of anti‐HCV(+) individuals no subsequent HCV‐RNA PCR was performed and only a low proportion of HIV/HCV coinfected patients achieved SVR …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Among our study population, one PWID presented with acute HCV infection at BL and showed persisting viraemia at FU. Although the overall test rate in our population was high, this goes in line with recently published findings from the EuroSIDA cohort, where in almost 20% of anti‐HCV(+) individuals no subsequent HCV‐RNA PCR was performed and only a low proportion of HIV/HCV coinfected patients achieved SVR …”
Section: Discussionsupporting
confidence: 90%
“…Since the termination of this study, interventions to increase linkage to care for HIV/HCV coinfected patients have been intensified in Vienna 47 and future data analyses will assess the epidemiological impact of these HCV microelimination strategies. Furthermore, similar to the EuroSIDA report,40 our observations are not limited to but also include time periods from the pre-DAA era. Since then, the reimbursement limitations for HCV DAA therapy was eliminated and modern pangenotypic DAA regimens have been available, which will most likely impact HCV epidemiology in Austria.While this study is limited by the lack of a standardized HCV testing protocol and some patients being lost to FU, our epidemiological results are essential for future HCV microelimination projects targeting the specific population of HIV+ individuals in Vienna and other parts of Austria.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…In total, around a quarter of all HIV/HCV co-infected individuals in EuroSIDA received anti-HCV treatment between 1998-2010, with an increasing trend over time and marked regional differences in the uptake of anti-HCV therapy across Europe [37]. Ongoing work aims to establish the continuum of HCV care, to monitor short-term and long-term uptake, efficacy, and adverse events to DAAs across Europe, and to monitor long-term risk of liver disease and other clinical outcomes [38,39].…”
Section: Assessing the Influence Of Hepatitis Co-infectionmentioning
confidence: 99%
“…Enforcing preventive strategies targeted to limiting the burden of these infections, including actively offering serological testing for HBV and HCV and HBV vaccination, could contribute to reduction of liver‐related mortality, especially among injecting drug users [40,41] and younger PWA. Furthermore, the introduction since 2015 of effective direct‐acting antivirals to treat HCV infection is expected to be particularly effective in reducing its prevalence, provided that barriers to test‐and‐treat are removed and a continuum of care is established among HCV/HIV‐coinfected individuals [42]. The follow‐up of individuals under HCV treatment should focus on medication compliance, side‐effect monitoring, and drug interaction management.…”
Section: Discussionmentioning
confidence: 99%